Paolo Masi - qui - Gensini, Valentina (SilvanaEditoriale, 2019)
The significant meeting between 'Le Murate. Progetti Arte Contemporanea' in Florence and Paolo Masi produced a site-specific work dedicated by this Florentine artist to this unique place with a long and articulated history.0The exhibition project is born from a direct comparison between the artist, environments and the history of the Murate city complex, in the sign of a new production. The entire district is reread by Masi as a place of memory linked to isolation, voluntary as in a convent, or forced, as in a prison. The exhibited works involve the entire monumental complex, from the interior spaces of Le Murate. Progetti Arte Contemporanea to public spaces such as the façade, the fountain in Madonna della Neve square or the interior of the semi-octagon. The relationship with the Murate cultural district makes this project a great public work that reflects on the history of this particular part of the city. 00Exhibition: Le Murate, Florence, Italy (09.2018-01.2019)
Diese Publikation erscheint anlässlich der gleichnamigen Ausstellung im Le Murate. Progetti Arte Contemporanea vom 13.09.2018-31.01.2019 in Florenz
Keywords: Masi, Paolo -- 1933-; Installation -- Kunst; Masi, Paolo / 1933- / Exhibitions; Ausstellungskatalog -- Le Murate. Progetti Arte Contemporanea -- 13.09.2018-31.01.2019 -- Florenz; Bildband